A pH-responsive Ti3C2T x Epoxy self-healing anticorrosive coating with shape memory and its preparation method

CN122917637APending Publication Date: 2026-10-16FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611364335.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明针对现有形状记忆环氧防腐涂层主要依赖被动阻隔和形状回复实现损伤闭合、难以主动抑制划痕区域腐蚀,以及Ti3C2Tx在聚合物基体中易团聚、易氧化且其高导电性可能促进金属基体电化学腐蚀等问题,提供了一种pH响应Ti3C2Tx基形状记忆自修复防腐涂层的制备方法,以实现涂层损伤后的光热驱动形状回复和腐蚀微区缓蚀剂响应释放,赋予涂层物理修复与主动防护相结合的智能防腐功能

Benefits of technology

[0017] 1. This invention uses accordion-shaped Ti3C2T xAs a functional matrix, it fully utilizes its two-dimensional layered structure, large specific surface area, and photothermal conversion properties. Ti3C2T x The laminations can extend the diffusion path of corrosive media such as water, oxygen and chloride ions in the coating, forming a labyrinth barrier effect, and can generate heat under near-infrared light, providing a heat source for the repair of damage to shape memory epoxy coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917637A_ABST
    Figure CN122917637A_ABST
Patent Text Reader

Abstract

This invention discloses a pH-responsive Ti3C2T x Shape memory epoxy self-healing anti-corrosion coating and its preparation method. This method utilizes dopamine in accordion-shaped Ti3C2T... x Surface in-situ polymerization to form Ti3C2T x @PDA, and induced in situ growth of ZIF-8 with zinc nitrate hexahydrate and 2-methylimidazole, and further loaded with sodium phytate using a combination of vacuum impregnation and atmospheric pressure loading to prepare Ti3C2T x @PDA-ZIF-8 / PA-Na composite material. This material was dispersed in a shape memory epoxy system composed of bisphenol A type epoxy resin, neopentyl glycol diglycidyl ether, and polyetheramine D230, and then coated and cured to obtain a self-healing anti-corrosion coating. This coating utilizes Ti3C2T x The two-dimensional shielding and photothermal conversion effects of ZIF-8, the pH-responsive release ability of ZIF-8, and the corrosion inhibition effect of sodium phytate enable photothermal-driven damage repair and active corrosion protection to work synergistically, thereby improving the long-term corrosion resistance of the metal matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of anti-corrosion coating materials, specifically relating to a pH-responsive Ti3C2T x The shape memory epoxy self-healing anti-corrosion coating significantly improves its anti-corrosion performance. Background Technology

[0002] Shape memory epoxy polymers possess excellent film-forming properties, mechanical properties, interfacial adhesion, and thermal stability. They can also close damaged areas of the coating through shape recovery under external stimuli, thus showing promising application prospects in the field of intelligent self-healing anti-corrosion coatings. A shape memory epoxy system formed by crosslinking bisphenol A type epoxy resin, neopentyl glycol diglycidyl ether, and polyetheramine D230 can achieve a coating with a certain degree of stiffness, toughness, and shape recovery capability by adjusting the ratio of soft and hard segments and the crosslinking network structure. However, traditional shape memory epoxy coatings mainly rely on the physical barrier effect of the polymer network for corrosion protection. When the coating is subjected to long-term immersion in corrosive media, mechanical impact, or external scratches, corrosive substances such as water, oxygen, and chloride ions can easily migrate to the metal substrate surface along internal defects and damage channels. Although the shape memory effect can promote scratch closure, it mainly achieves physical closure of the damaged area and cannot actively inhibit electrochemical corrosion that has already occurred at the scratch. Therefore, the continuous protection capability of a single shape memory repair mechanism for the metal substrate remains limited.

[0003] In recent years, Ti3C2T x As a novel two-dimensional material, Ti3C2T possesses a large specific surface area, abundant surface functional groups, excellent mechanical properties, and good photothermal conversion capabilities. x After the introduction of the polymer coating, its layered structure can extend the penetration path of corrosive media within the coating, forming a labyrinthine shielding effect, thereby improving the barrier performance of the coating; simultaneously, Ti3C2T x It can rapidly convert light energy into heat energy under near-infrared light irradiation, providing a heat source for triggering shape recovery and scratch closure of shape memory epoxy networks. However, Ti3C2T x The layers are prone to stacking and aggregation, resulting in limited dispersion stability and interfacial compatibility in the polymer matrix. Furthermore, it is susceptible to oxidation in aqueous and oxygen-containing environments, leading to structural and performance degradation. In addition, Ti3C2T... x It has high conductivity. When it forms a conductive path with the metal substrate and corrosive electrolyte after the coating is damaged, it may cause microgalvanic corrosion, which will accelerate the corrosion process of the metal substrate.

[0004] Therefore, how to deal with Ti3C2T xInterface modification was performed to improve its dispersibility and antioxidant properties while suppressing the corrosion-promoting effect that might be caused by its conductivity; and how to modify Ti3C2T x The combination of photothermal conversion performance and shape recovery capability of shape memory epoxy coating enables the coating to simultaneously achieve physical closure of scratches and active corrosion inhibition at the metal interface after damage. This is a technical problem that urgently needs to be solved to further improve the long-term anti-corrosion performance and post-damage protection and recovery capability of shape memory epoxy composite coating. Summary of the Invention

[0005] This invention addresses the shortcomings of existing shape memory epoxy anti-corrosion coatings, which primarily rely on passive barrier and shape recovery to achieve damage closure and are unable to actively inhibit corrosion in scratched areas, as well as Ti3C2T... x To address the issues of easy aggregation and oxidation in polymer matrices, and the potential for their high conductivity to promote electrochemical corrosion of metal matrices, a pH-responsive Ti3C2T method is proposed. x A method for preparing a shape memory self-healing anti-corrosion coating is proposed to achieve photothermal-driven shape recovery and responsive release of corrosion inhibitors in corrosion micro-areas after coating damage, thereby endowing the coating with intelligent anti-corrosion functions that combine physical repair and active protection. This method utilizes accordion-shaped Ti3C2T... x Using dopamine as a functional matrix, a polydopamine layer was formed by in-situ self-polymerization on its surface to prepare Ti3C2T. x @PDA; The abundant hydroxyl and amino groups on the surface of polydopamine can improve Ti3C2T x The dispersion stability and interfacial bonding between the Ti3C2T and the polymer matrix are improved, reducing lamellar aggregation and forming a protective layer to isolate moisture and oxygen, thus delaying the degradation of Ti3C2T. x The oxidation degradation reduces the likelihood of a continuous electron transport pathway forming between its highly conductive surface and the metal substrate. Subsequently, using zinc nitrate hexahydrate and 2-methylimidazole as raw materials, in Ti3C2T x ZIF-8 was grown in situ on the surface of a PDA, and sodium phytate was loaded into the pores and composite structure of ZIF-8 using a combination of reduced pressure impregnation and atmospheric pressure loading to prepare pH-responsive Ti3C2T. x @PDA-ZIF-8 / PA-Na anti-corrosion material; the anti-corrosion material is uniformly dispersed in a shape memory epoxy system composed of bisphenol A type epoxy resin, neopentyl glycol diglycidyl ether, and polyetheramine D230, coated onto the surface of a metal substrate, and cured into a film to obtain pH-responsive Ti3C2T. x A shape memory self-healing anti-corrosion coating. When the coating is damaged and exposed to near-infrared light, Ti3C2T... xIt can convert light energy into heat energy, triggering shape recovery in the shape memory epoxy network, promoting scratch closure and barrier structure restoration; when acidic changes occur in the corrosion micro-region, ZIF-8 undergoes responsive dissociation and promotes the release of sodium phytate. The released phytate ions complex with metal ions, forming a protective layer on the metal surface, thereby inhibiting metal dissolution and corrosion reactions. Combined with Ti3C2T x The labyrinthine barrier effect of the two-dimensional sheets on the corrosive medium forms a multi-synergistic protection mechanism of "pH-responsive active corrosion inhibition, photothermal-driven shape memory repair, two-dimensional physical shielding, and conductive pathway regulation", which significantly improves the long-term corrosion resistance of the coating and its ability to protect and recover after damage.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: This invention uses accordion-shaped Ti3C2T x Ti3C2T was prepared by in-situ polymerization of dopamine as the matrix. x @PDA, then ZIF-8 was grown in situ on its surface, and sodium phytate was loaded using a combination of vacuum impregnation and atmospheric pressure loading to obtain pH-responsive Ti3C2T x @PDA-ZIF-8 / PA-Na anti-corrosion material. This anti-corrosion material was dispersed in a shape memory epoxy system composed of bisphenol A type epoxy resin, neopentyl glycol diglycidyl ether, and polyetheramine D230. After coating and curing, a pH-responsive Ti3C2T was obtained. x A shape memory self-healing anti-corrosion coating is used. The coating utilizes ZIF-8 to achieve pH-responsive release of sodium phytate and utilizes Ti3C2T... x The photothermal conversion triggers the shape memory epoxy network recovery, achieving active corrosion inhibition and scratch closure.

[0007] The pH-responsive Ti3C2T x The preparation method of the shape memory epoxy self-healing anti-corrosion coating specifically includes the following steps: Step S1 Ti3C2T x @PDA preparation: Accordion-shaped Ti3C2T x Add the product to deionized water, then add tris(hydroxymethyl)aminomethane, and sonicate for 20 min to obtain Ti3C2T. x Dispersion; to the Ti3C2T x Dopamine hydrochloride was added to the dispersion, and the mixture was stirred for 15 min, followed by ultrasonic dispersion for 25 min. The mixture was then placed in a 60 ℃ water bath and stirred for 5 h. After the reaction, the product was separated by vacuum filtration, washed with deionized water, and finally freeze-dried to obtain polydopamine-modified accordion-shaped Ti3C2T. x Designated as Ti3C2T x@PDA; Step S2 Ti3C2T x Preparation of @PDA-ZIF-8: The Ti3C2T x PDA was added to methanol and ultrasonically dispersed for 15 min. Zinc nitrate hexahydrate was then added, and the mixture was ultrasonically dispersed for another 5 min followed by stirring for 30 min. 2-Methylimidazole was added to methanol, ultrasonicated until homogeneous, and then slowly added to the above mixture. After stirring for 30 min, the mixture was allowed to stand for 24 h. After the reaction was complete, the product was separated by filtration, washed three times with methanol, and dried at 55 °C for 24 h to obtain ZIF-8-coated polydopamine-modified accordion-shaped Ti3C2T. x Composite material, denoted as Ti3C2T x @PDA-ZIF-8; Step S3 pH response Ti3C2T x Preparation of @PDA-ZIF-8 / PA-Na anti-corrosion material: Sodium phytate and the Ti3C2T x @PDA-ZIF-8 was added to a reaction vessel containing methanol, thoroughly mixed, and ultrasonically dispersed for 10 min; then stirred and loaded under vacuum for 2 h, followed by stirring and loading under normal pressure for another 3 h; after the reaction was completed, the product was separated by vacuum filtration, washed with ethanol, and finally dried at 55 ℃ for 24 h to obtain sodium phytate-supported ZIF-8-coated polydopamine-modified accordion-shaped Ti3C2T. x Functional materials; Step S4 pH response Ti3C2T x Preparation of shape memory epoxy self-healing anti-corrosion coating: Weigh out pH-responsive Ti3C2T x The @PDA-ZIF-8 / PA-Na anti-corrosion material was added to a mixture of bisphenol A type epoxy resin and neopentyl glycol diglycidyl ether, ultrasonically treated for 30 minutes, and then continuously stirred for 4 hours. Subsequently, polyetheramine D230 curing agent was added and stirred for another half hour. The mixture was then coated onto a steel plate using a coating rod and cured in an atmospheric environment for 24 hours, followed by curing in a 55℃ oven for 12 hours to obtain pH-responsive Ti3C2T. x Shape memory epoxy self-healing anti-corrosion coating.

[0008] Furthermore, the dopamine hydrochloride and Ti3C2T mentioned in step S1 x The mass ratio is 1:1.

[0009] Furthermore, the Ti3C2T mentioned in step S1 xThe concentration of tris(hydroxymethyl)aminomethane in the dispersion was 10 mmol / L.

[0010] Furthermore, the Ti3C2T mentioned in step S2 x The mass ratio of PDA, zinc nitrate hexahydrate, and 2-methylimidazole is 1:10:20.

[0011] Furthermore, the sodium phytate and Ti3C2T mentioned in step S3 x The mass ratio of @PDA-ZIF-8 is 5:1.

[0012] Furthermore, the vacuum pressure in step S3 is -0.08 MPa.

[0013] Furthermore, in step S4, the mass ratio of bisphenol A type epoxy resin, neopentyl glycol diglycidyl ether, and polyetheramine D230 curing agent is 3.4:2.16:2.3.

[0014] Furthermore, the pH response Ti3C2T described in step S4 x The amount of @PDA-ZIF-8 / PA-Na anti-corrosion material added is 0.2~1.0 wt% of the mass of the mixture of bisphenol A type epoxy resin, neopentyl glycol diglycidyl ether and polyetheramine D230 curing agent, preferably 0.5 wt%.

[0015] In this invention, dopamine can undergo oxidative self-polymerization in Ti3C2T x A polydopamine layer forms on the surface, and the polydopamine surface contains abundant catechol groups, amino groups and other active groups, which is beneficial to improving the performance of Ti3C2T. x It improves the dispersion stability, antioxidant properties, and interfacial bonding with the polymer matrix, while also reducing the dispersion stability of Ti3C2T to a certain extent. x The high conductivity promotes corrosion. The polydopamine layer can also provide nucleation and anchoring sites for the in-situ growth of metal-organic framework materials. ZIF-8 has a large specific surface area and porous structure, which can serve as a loading carrier for corrosion inhibitors. It can also undergo responsive dissociation in the acidic environment of the corrosion micro-region, thereby achieving on-demand release of the corrosion inhibitor. Sodium phytate contains multiple phosphate groups, which can complex with metal ions and form a protective complex layer on the surface of the metal substrate. However, if it is directly added to the coating, it is prone to problems such as premature migration, rapid loss, and insufficient compatibility with the polymer matrix, making it difficult to achieve long-term, controllable active protection.

[0016] The significant advantages of this invention are:

[0017] 1. This invention uses accordion-shaped Ti3C2T xAs a functional matrix, it fully utilizes its two-dimensional layered structure, large specific surface area, and photothermal conversion properties. Ti3C2T x The laminations can extend the diffusion path of corrosive media such as water, oxygen and chloride ions in the coating, forming a labyrinth barrier effect, and can generate heat under near-infrared light, providing a heat source for the repair of damage to shape memory epoxy coatings.

[0018] 2. This invention utilizes dopamine to target Ti3C2T x Surface modification was performed to obtain Ti3C2T x @PDA. Polydopamine layers can improve Ti3C2T x It improves dispersion stability in reaction media and epoxy groups, reduces lamellar aggregation, and delays the degradation of Ti3C2T. x Oxidation reduces the risk of corrosion caused by the formation of a continuous conductive path between the metal matrix and the metal.

[0019] 3. This invention uses a polydopamine layer as the nucleation and bonding interface in Ti3C2T x ZIF-8 was grown in situ on the surface of a PDA, and sodium phytate was loaded onto it using a combination of vacuum impregnation and atmospheric pressure loading to prepare Ti3C2T. x @PDA-ZIF-8 / PA-Na corrosion-resistant material. This multi-level structure improves the load stability of sodium phytate and reduces migration, loss, and uneven dispersion problems that occur when it is directly added to the coating.

[0020] 4. This invention achieves a synergistic effect of pH-responsive active corrosion inhibition and photothermal-driven shape memory repair. After coating damage, the acidic environment of the corroded micro-regions promotes the responsive dissociation of ZIF-8 and releases sodium phytate. The phytate ions then complex with metal ions to form a protective layer; under near-infrared irradiation, Ti3C2T... x The photothermal effect triggers the shape memory epoxy network to recover its shape, promoting scratch closure, thus forming a multi-layered protection mechanism of "pH-responsive corrosion inhibition - photothermal self-repair - two-dimensional shielding - electronic transport regulation".

[0021] 5. This invention constructs a multifunctional integrated nano-hybrid anti-corrosion system, achieving the integration of shielding protection, active corrosion inhibition, and damage repair functions. Unlike traditional epoxy anti-corrosion coatings that primarily rely on physical barrier effects, this invention utilizes Ti3C2T... x The synergistic design of two-dimensional layers, ZIF-8 responsive carrier, and sodium phytate corrosion inhibitor enables the coating to simultaneously possess the capabilities of corrosive media barrier, corrosion response release, and damage repair, achieving a transformation from passive protection to intelligent active protection.

[0022] 6. This invention proposes a dual-response self-healing strategy based on the synergistic driving of corrosion environment response and external photothermal stimulation. When the coating is subjected to mechanical damage, the acidic environment generated by the corrosion micro-regions can trigger the ZIF-8 structural response and release sodium phytate, achieving local active corrosion inhibition; simultaneously, Ti3C2T x The photothermal conversion effect can drive the shape memory epoxy network to recover its shape, promote the closure of the scratched area, and thus achieve the synergistic effect of chemical protection and physical repair.

[0023] 7. This invention realizes the functional utilization of two-dimensional MXene materials in anti-corrosion coatings, solving the problem that their high conductivity may induce corrosion promotion. By constructing a PDA interface layer and further loading a ZIF-8 structure, the Ti3C2T... x The electron transport behavior between MXene and the metal substrate reduces the risk of galvanic corrosion caused by direct contact between MXene and the metal substrate, while retaining its excellent two-dimensional shielding and photothermal conversion performance, providing a new design strategy for the application of MXene in the field of intelligent corrosion protection. Attached Figure Description

[0024] Figure 1 For (a)Ti3C2T x (b)Ti3C2T x @PDA、(c)Ti3C2T x @PDA-ZIF-8、(d)Ti3C2T x SEM image of @PDA-ZIF-8 / PA-Na; Figure 2 Ti3C2T x (abbreviated as T), Ti3C2T x @PDA (TP for short), Ti3C2T x @PDA-ZIF-8 (TPZ for short), Ti3C2T x FT-IR plot of @PDA-ZIF-8 / PA-Na (TPZS for short); Figure 3 Ti3C2T x (abbreviated as T), Ti3C2T x @PDA (TP for short), Ti3C2T x @PDA-ZIF-8 (TPZ for short), Ti3C2T x XRD pattern of @PDA-ZIF-8 / PA-Na (TPZS for short); Figure 4 The EIS spectra of the composite coatings (complete) in Examples 1-3 are shown. Figure 5Electrochemical impedance spectroscopy of the coatings in Comparative Examples 1-4 and Example 2 before near-infrared irradiation; (1) Comparative Example 1; (2) Comparative Example 2; (3) Comparative Example 3; (4) Comparative Example 4; (5) Example 2; Figure 6 The scratch electrochemical impedance spectra of the coatings of Comparative Examples 1-4 and Example 2 after near-infrared irradiation are shown; (1) Comparative Example 1; (2) Comparative Example 2; (3) Comparative Example 3; (4) Comparative Example 4; (5) Example 2. Detailed Implementation

[0025] To make the content of this invention easier to understand, the technical solution of this invention will be further described below with reference to specific embodiments, but this invention is not limited thereto.

[0026] Example 1 (0.2wt% pH-responsive Ti3C2T) x (Base shape memory epoxy self-healing anti-corrosion coating) (1) Ti3C2T x @PDA Preparation 200 mg of accordion-shaped Ti3C2T x (Purchased from Jinan Sanchuan New Material Technology Co., Ltd., product model: MXene Accordion) Add to 100 mL of deionized water, then add 121 mg of tris(hydroxymethyl)aminomethane to achieve a concentration of 10 mmol / L in the resulting system. Disperse ultrasonically for 20 min to obtain Ti3C2T. x Dispersion; to the Ti3C2T x 200 mg of dopamine hydrochloride was added to the dispersion, and the mixture was stirred for 15 min, followed by ultrasonic dispersion for 25 min. The mixture was then placed in a 60 ℃ water bath and stirred for 5 h. After the reaction, the product was separated by vacuum filtration, washed with deionized water, and finally freeze-dried to obtain polydopamine-modified accordion-shaped Ti3C2T. x Designated as Ti3C2T x @PDA.

[0027] (2) Ti3C2T x Preparation of @PDA-ZIF-8 100 mg of the aforementioned Ti3C2T x@PDA was added to 30 mL of methanol and ultrasonically dispersed for 15 min. Then, 0.80325 g of zinc nitrate hexahydrate was added, and ultrasonic dispersion was continued for 5 min, followed by stirring for 30 min. 1.6071 g of 2-methylimidazole was added to 20 mL of methanol, ultrasonicated until homogeneous, and then slowly added to the above mixture. After stirring for 30 min, the mixture was allowed to stand for 24 h. After the reaction was completed, the product was separated by vacuum filtration, washed three times with methanol, and dried at 55 ℃ for 24 h to obtain ZIF-8-coated polydopamine-modified accordion-shaped Ti3C2T. x Composite material, denoted as Ti3C2T x @PDA-ZIF-8.

[0028] (3) pH response Ti3C2T x Preparation of @PDA-ZIF-8 / PA-Na anti-corrosion material 500 mg of sodium phytate and 100 mg of the aforementioned Ti3C2T x @PDA-ZIF-8 was added to a reaction vessel containing 50 mL of methanol, thoroughly mixed, and ultrasonically dispersed for 10 min. The mixture was then stirred and loaded under vacuum pressure of -0.08 MPa for 2 h, followed by stirring and loading under normal pressure for another 3 h. After the reaction was complete, the product was separated by vacuum filtration, washed with ethanol, and finally dried at 55 ℃ for 24 h to obtain sodium phytate-supported ZIF-8-coated polydopamine-modified accordion-shaped Ti3C2T. x Functional materials.

[0029] (4) pH response Ti3C2T x Preparation of shape memory epoxy self-healing anti-corrosion coating Weigh 15.7 mg of pH-responsive Ti3C2T x The @PDA-ZIF-8 / PA-Na anti-corrosion material was added to a mixture of 3.4g bisphenol A epoxy resin and 2.16g neopentyl glycol diglycidyl ether. After ultrasonic treatment for 30 minutes, the mixture was stirred continuously for 4 hours. Then, 2.3g polyetheramine D230 curing agent was added and the mixture was stirred continuously for half an hour. Finally, it was coated onto a steel plate using an 80μm coating rod and cured in an atmospheric environment for 24 hours. Then, it was placed in a 55℃ oven for 12 hours to obtain pH-responsive Ti3C2T. x Shape memory epoxy self-healing anti-corrosion coating.

[0030] Example 2 (0.5wt% pH-responsive Ti3C2T) x (Base shape memory epoxy self-healing anti-corrosion coating) (1) Ti3C2T x @PDA Preparation 200 mg of accordion-shaped Ti3C2T x Add 100 mL of deionized water, followed by 121 mg of tris(hydroxymethyl)aminomethane to achieve a concentration of 10 mmol / L in the resulting system. Disperse by sonication for 20 min to obtain Ti3C2T. x Dispersion; to the Ti3C2T x 200 mg of dopamine hydrochloride was added to the dispersion, and the mixture was stirred for 15 min, followed by ultrasonic dispersion for 25 min. The mixture was then placed in a 60 ℃ water bath and stirred for 5 h. After the reaction, the product was separated by vacuum filtration, washed with deionized water, and finally freeze-dried to obtain polydopamine-modified accordion-shaped Ti3C2T. x Designated as Ti3C2T x @PDA.

[0031] (2) Ti3C2T x Preparation of @PDA-ZIF-8 100 mg of the aforementioned Ti3C2T x @PDA was added to 30 mL of methanol and ultrasonically dispersed for 15 min. Then, 0.80325 g of zinc nitrate hexahydrate was added, and ultrasonic dispersion was continued for 5 min, followed by stirring for 30 min. 1.6071 g of 2-methylimidazole was added to 20 mL of methanol, ultrasonicated until homogeneous, and then slowly added to the above mixture. After stirring for 30 min, the mixture was allowed to stand for 24 h. After the reaction was completed, the product was separated by vacuum filtration, washed three times with methanol, and dried at 55 ℃ for 24 h to obtain ZIF-8-coated polydopamine-modified accordion-shaped Ti3C2T. x Composite material, denoted as Ti3C2T x @PDA-ZIF-8.

[0032] (3) pH response Ti3C2T x Preparation of @PDA-ZIF-8 / PA-Na anti-corrosion material 500 mg of sodium phytate and 100 mg of the aforementioned Ti3C2T x @PDA-ZIF-8 was added to a reaction vessel containing 50 mL of methanol, thoroughly mixed, and ultrasonically dispersed for 10 min. The mixture was then stirred and loaded under vacuum pressure of -0.08 MPa for 2 h, followed by stirring and loading under normal pressure for another 3 h. After the reaction was complete, the product was separated by vacuum filtration, washed with ethanol, and finally dried at 55 ℃ for 24 h to obtain sodium phytate-supported ZIF-8-coated polydopamine-modified accordion-shaped Ti3C2T. x Functional materials.

[0033] (4) pH response Ti3C2Tx Preparation of shape memory epoxy self-healing anti-corrosion coating Weigh 39.3 mg of pH-responsive Ti3C2T x The @PDA-ZIF-8 / PA-Na anti-corrosion material was added to a mixture of 3.4g bisphenol A epoxy resin and 2.16g neopentyl glycol diglycidyl ether. After ultrasonic treatment for 30 minutes, the mixture was stirred continuously for 4 hours. Then, 2.3g polyetheramine D230 curing agent was added and the mixture was stirred continuously for half an hour. Finally, it was coated onto a steel plate using an 80μm coating rod and cured in an atmospheric environment for 24 hours. Then, it was placed in a 55℃ oven for 12 hours to obtain pH-responsive Ti3C2T. x Shape memory epoxy self-healing anti-corrosion coating.

[0034] Example 3 (1.0wt% pH-responsive Ti3C2T) x (Base shape memory epoxy self-healing anti-corrosion coating) (1) Ti3C2T x @PDA Preparation 200 mg of accordion-shaped Ti3C2T x Add 100 mL of deionized water, followed by 121 mg of tris(hydroxymethyl)aminomethane to achieve a concentration of 10 mmol / L in the resulting system. Disperse by sonication for 20 min to obtain Ti3C2T. x Dispersion; to the Ti3C2T x 200 mg of dopamine hydrochloride was added to the dispersion, and the mixture was stirred for 15 min, followed by ultrasonic dispersion for 25 min. The mixture was then placed in a 60 ℃ water bath and stirred for 5 h. After the reaction, the product was separated by vacuum filtration, washed with deionized water, and finally freeze-dried to obtain polydopamine-modified accordion-shaped Ti3C2T. x Designated as Ti3C2T x @PDA.

[0035] (2) Ti3C2T x Preparation of @PDA-ZIF-8 100 mg of the aforementioned Ti3C2T x @PDA was added to 30 mL of methanol and ultrasonically dispersed for 15 min. Then, 0.80325 g of zinc nitrate hexahydrate was added, and ultrasonic dispersion was continued for 5 min, followed by stirring for 30 min. 1.6071 g of 2-methylimidazole was added to 20 mL of methanol, ultrasonicated until homogeneous, and then slowly added to the above mixture. After stirring for 30 min, the mixture was allowed to stand for 24 h. After the reaction was completed, the product was separated by vacuum filtration, washed three times with methanol, and dried at 55 ℃ for 24 h to obtain ZIF-8-coated polydopamine-modified accordion-shaped Ti3C2T.x Composite material, denoted as Ti3C2T x @PDA-ZIF-8.

[0036] (3) pH response Ti3C2T x Preparation of @PDA-ZIF-8 / PA-Na anti-corrosion material 500 mg of sodium phytate and 100 mg of the aforementioned Ti3C2T x @PDA-ZIF-8 was added to a reaction vessel containing 50 mL of methanol, thoroughly mixed, and ultrasonically dispersed for 10 min. The mixture was then stirred and loaded under vacuum pressure of -0.08 MPa for 2 h, followed by stirring and loading under normal pressure for another 3 h. After the reaction was complete, the product was separated by vacuum filtration, washed with ethanol, and finally dried at 55 ℃ for 24 h to obtain sodium phytate-supported ZIF-8-coated polydopamine-modified accordion-shaped Ti3C2T. x Functional materials.

[0037] (4) pH response Ti3C2T x Preparation of shape memory epoxy self-healing anti-corrosion coating Weigh out 78.6 mg of pH-responsive Ti3C2T x The @PDA-ZIF-8 / PA-Na anti-corrosion material was added to a mixture of 3.4g bisphenol A epoxy resin and 2.16g neopentyl glycol diglycidyl ether. After ultrasonic treatment for 30 minutes, the mixture was stirred continuously for 4 hours. Then, 2.3g polyetheramine D230 curing agent was added and the mixture was stirred continuously for half an hour. Finally, it was coated onto a steel plate using an 80μm coating rod and cured in an atmospheric environment for 24 hours. Then, it was placed in a 55℃ oven for 12 hours to obtain pH-responsive Ti3C2T. x Shape memory epoxy self-healing anti-corrosion coating.

[0038] Comparative Example 1 (Pure shape memory epoxy self-healing anti-corrosion coating)

[0039] (1) Preparation of pure shape memory epoxy self-healing anti-corrosion coating: Weigh 3.4g of bisphenol A epoxy resin and 2.16g of neopentyl glycol diglycidyl ether, mix and stir for 4 hours. Then add 2.3g of polyetheramine D230 curing agent and continue stirring for half an hour. Then coat it onto a steel plate with an 80μm coating rod, cure in an atmospheric environment for 24 hours, and then place it in a 55℃ oven for 12 hours.

[0040] Comparative Example 2 (0.5wt% Ti3C2T) x Shape memory epoxy self-healing anti-corrosion coating (1) Ti3C2T x Preparation of shape memory epoxy self-healing anti-corrosion coating: Weigh out 39.3 mg Ti3C2T x The anti-corrosion material was added to a mixture of 3.4g bisphenol A epoxy resin and 2.16g neopentyl glycol diglycidyl ether, and ultrasonically treated for 30 minutes followed by continuous stirring for 4 hours. Then, 2.3g polyetheramine D230 curing agent was added and stirred for another half hour. The mixture was then coated onto a steel plate using an 80μm coating rod and cured in an atmospheric environment for 24 hours. Finally, it was cured in a 55℃ oven for 12 hours to obtain Ti3C2T. x Shape memory epoxy self-healing anti-corrosion coating.

[0041] Comparative Example 3 (0.5wt% Ti3C2T) x @PDA Shape Memory Epoxy Self-Healing Anti-corrosion Coating) (1) Ti3C2T x @PDA preparation: 200 mg of accordion-shaped Ti3C2T x Add 100 mL of deionized water, followed by 121 mg of tris(hydroxymethyl)aminomethane to achieve a concentration of 10 mmol / L in the resulting system. Disperse by sonication for 20 min to obtain Ti3C2T. x Dispersion; to the Ti3C2T x 200 mg of dopamine hydrochloride was added to the dispersion, and the mixture was stirred for 15 min, followed by ultrasonic dispersion for 25 min. The mixture was then placed in a 60 ℃ water bath and stirred for 5 h. After the reaction, the product was separated by vacuum filtration, washed with deionized water, and finally freeze-dried to obtain polydopamine-modified accordion-shaped Ti3C2T. x Designated as Ti3C2T x @PDA.

[0042] (2) Ti3C2T x Preparation of PDA shape memory epoxy self-healing anti-corrosion coating Weigh out 39.3 mg Ti3C2T x The PDA anti-corrosion material was added to a mixture of 3.4g bisphenol A epoxy resin and 2.16g neopentyl glycol diglycidyl ether. After ultrasonic treatment for 30 minutes, the mixture was stirred continuously for 4 hours. Then, 2.3g polyetheramine D230 curing agent was added and the mixture was stirred continuously for half an hour. Finally, it was coated onto a steel plate using an 80μm coating rod and cured in an atmospheric environment for 24 hours. Then, it was placed in a 55℃ oven for 12 hours to obtain Ti3C2T. x Shape memory epoxy self-healing anti-corrosion coating.

[0043] Comparative Example 4 (0.5wt% Ti3C2T) x @PDA-ZIF-8 Shape Memory Epoxy Self-Healing Anti-corrosion Coating) (1) Ti3C2T x @PDA preparation: 200 mg of accordion-shaped Ti3C2T x Add 100 mL of deionized water, followed by 121 mg of tris(hydroxymethyl)aminomethane to achieve a concentration of 10 mmol / L in the resulting system. Disperse by sonication for 20 min to obtain Ti3C2T. x Dispersion; to the Ti3C2T x 200 mg of dopamine hydrochloride was added to the dispersion, and the mixture was stirred for 15 min, followed by ultrasonic dispersion for 25 min. The mixture was then placed in a 60 ℃ water bath and stirred for 5 h. After the reaction, the product was separated by vacuum filtration, washed with deionized water, and finally freeze-dried to obtain polydopamine-modified accordion-shaped Ti3C2T. x Designated as Ti3C2T x @PDA.

[0044] (2) Ti3C2T x Preparation of @PDA-ZIF-8 100 mg of the aforementioned Ti3C2T x @PDA was added to 30 mL of methanol and ultrasonically dispersed for 15 min. Then, 0.80325 g of zinc nitrate hexahydrate was added, and ultrasonic dispersion was continued for 5 min, followed by stirring for 30 min. 1.6071 g of 2-methylimidazole was added to 20 mL of methanol, ultrasonicated until homogeneous, and then slowly added to the above mixture. After stirring for 30 min, the mixture was allowed to stand for 24 h. After the reaction was completed, the product was separated by vacuum filtration, washed three times with methanol, and dried at 55 ℃ for 24 h to obtain ZIF-8-coated polydopamine-modified accordion-shaped Ti3C2T. x Composite material, denoted as Ti3C2T x @PDA-ZIF-8.

[0045] (3) Ti3C2T x Preparation of @PDA-ZIF-8 Shape Memory Epoxy Self-Healing Anti-corrosion Coating Weigh out 39.3 mg Ti3C2T x @PDA-ZIF-8 anti-corrosion material was added to a mixture of 3.4g bisphenol A epoxy resin and 2.16g neopentyl glycol diglycidyl ether. After ultrasonic treatment for 30 minutes, the mixture was stirred continuously for 4 hours. Then, 2.3g polyetheramine D230 curing agent was added and the mixture was stirred continuously for half an hour. Finally, it was coated onto a steel plate using an 80μm coating rod and cured in an atmospheric environment for 24 hours. Then, it was placed in a 55℃ oven for 12 hours to obtain Ti3C2T. x Shape memory epoxy self-healing anti-corrosion coating.

[0046] Effect verification

[0047] pH-responsive Ti3C2T prepared in Example 2 x pH response tests were performed on the @PDA-ZIF-8 / PA-Na anti-corrosion material; and the anti-corrosion performance tests were performed on the shape memory epoxy self-healing anti-corrosion coatings prepared in Examples 1-3 and Comparative Examples 1-4, respectively. The specific methods and results are as follows: Ti3C2T x @PDA-ZIF-8 / PA-Na Corrosion-Resistant Material pH Response Test The Ti3C2T used in Example 2 was studied using an ICP-OES tester. x pH-responsive release behavior of @PDA-ZIF-8 / PA-Na preservatives. Weigh 100 mg of Ti3C2T... x The @PDA-ZIF-8 / PA-Na anticorrosive material was soaked in 100 mL of 3.5 wt% NaCl solution with pH values ​​of 3, 7 and 11 for 24 h. After centrifugation, the supernatant was collected for ICP-OES testing to determine the concentrations of P and Zn elements in the solution. The test results are shown in Table 1.

[0048] Table 1 pH Response Test

[0049] As shown in Table 1, the Ti3C2T used in Example 2 x The @PDA-ZIF-8 / PA-Na corrosion-resistant material exhibits a significant pH-responsive release behavior. Under acidic conditions, the release concentrations of phosphorus (P) and zinc (Zn) reached 32.91 ppm and 6.919 ppm, respectively, indicating that the acidic environment promotes the responsive dissociation of the ZIF-8 structure and facilitates the release of phosphorus-containing corrosion-inhibiting components. Under neutral conditions, the release concentrations of P and Zn decreased to 1.62 ppm and 0.157 ppm, respectively, indicating that the composite material has good stability in a neutral environment and can effectively inhibit the premature release of functional components. Under alkaline conditions, the release concentration of P increased to 27.31 ppm, while the release concentration of Zn was only 0.234 ppm, indicating that the alkaline environment mainly promotes the release of phosphorus-containing components from the composite material, while the ZIF-8 framework did not undergo significant large-scale dissociation. Therefore, the prepared Ti3C2T x @PDA-ZIF-8 / PA-Na corrosion-resistant material exhibits significant environmental pH response characteristics, demonstrating differentiated functional component release behavior under various corrosive microenvironments.

[0050] Corrosion resistance test

[0051] The corrosion resistance of the coating was studied using an electrochemical workstation and electrochemical impedance spectroscopy (EIS). The EIS test frequency range was 10 Hz. -2 ~10 5 Hz, the amplitude of the sinusoidal signal is 20mV. The electrolytic cell adopts a three-electrode system, and the steel plate coated with an organic coating (with a 1cm diameter) 2 A circular test area was used as the working electrode, and a saturated calomel electrode and a platinum wire were used as the reference electrode and counter electrode, respectively. The sample was immersed in a 3.5 wt% NaCl solution for EIS electrochemical performance testing.

[0052] like Figure 4 As shown, the pH-responsive Ti3C2T prepared in Examples 1-3 were respectively tested. x Long-term electrochemical impedance spectroscopy was performed on the shape memory self-healing anti-corrosion coatings. The results showed that all three coatings exhibited high low-frequency impedance moduli during the initial immersion period, and the impedance moduli only decreased to a certain extent with prolonged immersion time. After 60 days of immersion, the impedance moduli of all three coatings remained at 10 at 0.01 Hz. 8.5 A phase angle above Ω and maintaining a high phase angle over a wide frequency range indicates that the prepared coating can effectively delay the migration of corrosive media to the metal substrate, exhibiting good long-term shielding and corrosion resistance. Among them, the 0.5 wt% composite material coating prepared in Example 2 has the highest initial low-frequency impedance, which remains high and tends to stabilize after long-term immersion, demonstrating superior overall corrosion resistance compared to Examples 1 and 3. In Example 1, the amount of composite material added was relatively low, resulting in a relatively limited barrier network. In Example 3, further increasing the filler content did not significantly improve corrosion resistance, indicating that excessive addition may cause composite material agglomeration or interface defects. Therefore, the 0.5 wt% addition amount used in Example 2 has superior long-term corrosion resistance within the experimental range of this invention.

[0053] like Figure 5 , 6 As shown, artificial scratches approximately 1 cm in length and 10 μm in width were created on the coatings prepared in Comparative Examples 1-4 and Example 2 using a scratching tool. The scratches penetrated the coating and exposed the underlying steel substrate. The scratched coatings were then subjected to near-infrared irradiation treatment using a near-infrared light source with a wavelength of 808 nm and a power density of 1.0 W·cm². -2 The irradiation distance between the light source and the coating surface was 10 cm, and the irradiation was continuous for 5 minutes. After the irradiation, the electrochemical performance of the treated scratched coating was tested to evaluate the effect of near-infrared photothermal effect on the recovery of the protective performance of the damaged area of ​​the shape memory epoxy coating. Comparative Example 1 was a pure shape memory epoxy self-healing anti-corrosion coating, and Comparative Example 2 was a 0.5 wt% Ti3C2T... xShape memory epoxy self-healing anti-corrosion coating, Comparative Example 3: 0.5 wt% Ti3C2T x @PDA shape memory epoxy self-healing anti-corrosion coating, Comparative Example 4: 0.5 wt% Ti3C2T x @PDA-ZIF-8 shape memory epoxy self-healing anti-corrosion coating, Example 2 is 0.5 wt% Ti3C2T x @PDA-ZIF-8 / PA-Na shape memory epoxy self-healing anti-corrosion coating. Results showed that before light irradiation, the impedance of the scratched coatings in Comparative Examples 1-4 and Example 2 changed to varying degrees with immersion time. Some phase angle curves showed broadening or multiple time constant characteristics, indicating that the corrosive medium had penetrated along the scratch area to the coating / metal interface. After near-infrared light irradiation, the low-frequency impedance of each group of coatings generally increased, and the peak phase angle and high phase angle frequency range recovered to varying degrees, indicating that the thermal effect generated by light irradiation can trigger shape recovery of the shape memory epoxy network and promote scratch closure. Among them, the Ti3C2T prepared in Example 2... x The @PDA-ZIF-8 / PA-Na shape memory epoxy self-healing anti-corrosion coating exhibits high and stable low-frequency impedance after light exposure, maintaining approximately 10 after immersion for 72 hours. 5 The Ω-level value indicates that it possesses good post-damage protection retention capability. The above results demonstrate that Ti3C2T... x The photothermal conversion effect can promote the physical closure of coating scratches. Sodium phytate loaded with ZIF-8 can be released in response to corrosion micro-areas and form an interface protective layer. Together, they achieve synergistic protection of photothermal driven shape memory repair and pH-responsive active corrosion inhibition, thereby improving the electrochemical protection performance of the scratch coating.

[0054] like Figure 1 (a) represents Ti3C2T x The scanning electron microscope image shows a typical accordion-like multilayer structure with clearly arranged layers and open gaps between them. After dopamine modification, Figure 1 The Ti3C2T shown in (b) x @PDA retains its original layered framework, but the surface of its layers becomes rougher and the edges tend to be rounded, indicating that polydopamine has been coated onto Ti3C2T. x The surface was intact, and the modification process did not significantly damage its accordion-like structure. Figure 1 As can be seen in (c), Ti3C2T x The presence of numerous particulate materials on the surface and between the layers of @PDA-ZIF-8 indicates that ZIF-8 plays a crucial role in the modification of Ti3C2T by polydopamine. x In-situ nucleation and growth occur on the surface. After loading with sodium phytate, as... Figure 1As shown in (d), the composite material retains its overall layered structure, with a denser surface particle coating and further filling of gaps between some particles and lamellae. These results indicate that the stepwise modification and loading processes did not significantly damage Ti3C2T. x The accordion-shaped framework helps to retain its two-dimensional labyrinth barrier effect and photothermal conversion performance, while forming a multi-level composite structure with ZIF-8 loading and sodium phytate storage function.

[0055] like Figure 2 As shown, Ti3C2T x At approximately 3400 cm -1 The OH stretching vibration absorption is observed at the surface, and surface end-group correlated absorptions such as CO, CF, and Ti-O appear in the low to medium wavenumber region. After dopamine modification, Ti3C2T exhibits... x @PDA at approximately 3400 cm -1 The enhanced OH / NH broad absorption band at Ti3C2T, along with the characteristic absorptions of CH, aromatic ring C=C, C=N, and CN, indicates that polydopamine has been coated onto Ti3C2T. x Surface. After in-situ growth of ZIF-8, Ti3C2T x The presence of imidazole ring-related vibrations and characteristic absorptions of the Zn-N coordination bond in @PDA-ZIF-8 indicates successful ZIF-8 formation. After loading with sodium phytate, Ti3C2T... x The absorption of @PDA-ZIF-8 / PA-Na is significantly enhanced in the wavenumber range related to the phosphate group. Combined with the P elemental analysis results, this indicates that sodium phytate has been loaded into the composite material. The final composite material retains the main characteristic absorptions of each component, demonstrating that the stepwise modification method can maintain the absorption of Ti3C2T. x While maintaining the basic structure, it also achieves PDA coating, in-situ growth of ZIF-8, and sodium phytate loading.

[0056] like Figure 3 As shown, Ti3C2T x The Ti3C2T exhibits characteristic diffraction peaks of the (002) crystal plane in the low-angle region, while retaining diffraction characteristics of the (004), (006), and (110) crystal planes, indicating that it possesses a complete layered crystal structure. After dopamine modification, Ti3C2T… x @PDA still retains Ti3C2T x The main characteristic peaks were observed, but the peak intensity decreased, indicating that the amorphous polydopamine layer had been coated on Ti3C2T. x The surface was intact, and its layered framework was not significantly damaged. After in-situ growth of ZIF-8, Ti3C2T... x@PDA-ZIF-8 exhibits characteristic diffraction peaks of ZIF-8 at approximately 7.3°, 10.4°, 12.7°, 14.7°, 16.4°, and 18.0°, indicating successful ZIF-8 formation. After loading with sodium phytate, Ti3C2T... x @PDA-ZIF-8 / PA-Na still retains ZIF-8 and Ti3C2T. x The main diffraction characteristics show that some peak intensities are reduced, indicating that the sodium phytate loading process did not significantly damage the main crystal structure of the composite material, and that sodium phytate exists in the composite material in a highly dispersed or amorphous state.

[0057] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.

Claims

1. A pH-responsive Ti3C2T x A method for preparing a shape memory epoxy self-healing anti-corrosion coating, characterized in that: Accordion-shaped Ti3C2T x Using dopamine as the matrix, polydopamine-modified Ti3C2T is formed through dopamine self-polymerization. x Using zinc nitrate hexahydrate and 2-methylimidazole as raw materials, ZIF-8 was grown in situ on its surface and then loaded with sodium phytate to prepare sodium phytate / ZIF-8 / polydopamine modified Ti3C2T. x Composite material; the composite material is added to a shape memory epoxy system composed of bisphenol A type epoxy resin, neopentyl glycol diglycidyl ether and polyetheramine, and then coated and cured to obtain a self-healing anti-corrosion coating.

2. The pH-responsive Ti3C2T according to claim 1 x A method for preparing a shape memory epoxy self-healing anti-corrosion coating, characterized in that, Includes the following steps: Step S1 Ti3C2T x @PDA preparation: Accordion-shaped Ti3C2T x Add the product to deionized water, then add tris(hydroxymethyl)aminomethane, and sonicate for 20 min to obtain Ti3C2T. x Dispersion; to the Ti3C2T x Dopamine hydrochloride was added to the dispersion, and the mixture was stirred for 15 min, followed by ultrasonic dispersion for 25 min. The mixture was then placed in a 60 ℃ water bath and stirred for 5 h. After the reaction, the product was separated by vacuum filtration, washed with deionized water, and finally freeze-dried to obtain polydopamine-modified accordion-shaped Ti3C2T. x Designated as Ti3C2T x @PDA; Step S2 Ti3C2T x Preparation of @PDA-ZIF-8: The Ti3C2T x PDA was added to methanol and ultrasonically dispersed for 15 min. Zinc nitrate hexahydrate was then added, and the mixture was ultrasonically dispersed for another 5 min followed by stirring for 30 min. 2-Methylimidazole was added to methanol, ultrasonicated until homogeneous, and then slowly added to the mixture. After stirring for 30 min, the mixture was allowed to stand for 24 h. After the reaction was complete, the product was separated by filtration, washed three times with methanol, and dried at 55 °C for 24 h to obtain ZIF-8-coated polydopamine-modified accordion-shaped Ti3C2T. x Composite material, denoted as Ti3C2T x @PDA-ZIF-8; Step S3 pH response Ti3C2T x Preparation of @PDA-ZIF-8 / PA-Na anti-corrosion material: Sodium phytate and the Ti3C2T x @PDA-ZIF-8 was added to a reaction vessel containing methanol, thoroughly mixed, and ultrasonically dispersed for 10 min; then stirred and loaded under vacuum for 2 h, followed by stirring and loading under normal pressure for another 3 h; after the reaction was completed, the product was separated by vacuum filtration, washed with ethanol, and finally dried at 55 ℃ for 24 h to obtain sodium phytate-supported ZIF-8-coated polydopamine-modified accordion-shaped Ti3C2T. x Functional material, denoted as pH-responsive Ti3C2T x @PDA-ZIF-8 / PA-Na anti-corrosion material; Step S4 pH response Ti3C2T x Preparation of shape memory epoxy self-healing anti-corrosion coating: Weigh out pH-responsive Ti3C2T x The @PDA-ZIF-8 / PA-Na anti-corrosion material was added to a mixture of bisphenol A type epoxy resin and neopentyl glycol diglycidyl ether, ultrasonically treated for 30 minutes, and then continuously stirred for 4 hours. Subsequently, polyetheramine D230 curing agent was added and stirred for another half hour. The mixture was then coated onto a steel plate using a coating rod and cured in an atmospheric environment for 24 hours, followed by curing in a 55℃ oven for 12 hours to obtain pH-responsive Ti3C2T. x Shape memory epoxy self-healing anti-corrosion coating.

3. The pH-responsive Ti3C2T according to claim 2 x A method for preparing a shape memory epoxy self-healing anti-corrosion coating, characterized in that: The dopamine hydrochloride and Ti3C2T mentioned in step S1 x The mass ratio is 1:

1.

4. The pH-responsive Ti3C2T according to claim 2 x A method for preparing a shape memory epoxy self-healing anti-corrosion coating, characterized in that: The Ti3C2T mentioned in step S1 x The concentration of tris(hydroxymethyl)aminomethane in the dispersion was 10 mmol / L.

5. The pH-responsive Ti3C2T according to claim 2 x A method for preparing a shape memory epoxy self-healing anti-corrosion coating, characterized in that: The Ti3C2T mentioned in step S2 x The mass ratio of PDA, zinc nitrate hexahydrate, and 2-methylimidazole is 1:10:

20.

6. The pH-responsive Ti3C2T according to claim 2 x A method for preparing a shape memory epoxy self-healing anti-corrosion coating, characterized in that: The sodium phytate and Ti3C2T mentioned in step S3 x The mass ratio of @PDA-ZIF-8 is 5:

1.

7. The pH-responsive Ti3C2T according to claim 2 x A method for preparing a shape memory epoxy self-healing anti-corrosion coating, characterized in that: The vacuum pressure in step S3 is -0.08 MPa.

8. The pH-responsive Ti3C2T according to claim 2 x A method for preparing a shape memory epoxy self-healing anti-corrosion coating, characterized in that: In step S4, the mass ratio of bisphenol A epoxy resin, neopentyl glycol diglycidyl ether, and polyetheramine D230 curing agent is 3.4:2.16:2.

3.

9. The pH-responsive Ti3C2T according to claim 2 x A method for preparing a shape memory epoxy self-healing anti-corrosion coating, characterized in that: The pH response Ti3C2T described in step S4 x The amount of @PDA-ZIF-8 / PA-Na anti-corrosion material added is 0.2~1.0 wt% of the mass of the mixture of bisphenol A type epoxy resin, neopentyl glycol diglycidyl ether and polyetheramine D230 curing agent.

10. pH-responsive Ti3C2T prepared by the method according to any one of claims 1-9 x Shape memory epoxy self-healing anti-corrosion coating.